Distributed control for polygeneration microgrids: A Dynamic Market Mechanism approach. (April 2022) - Nudell, Thomas R.; Brignone, Massimo; Robba, Michela; Bonfiglio, Andrea; Ferro, Giulio; Delfino, Federico; Annaswamy, Anuradha M.
Abstract: This paper develops a Dynamic Market Mechanism ( μ DMM) to optimally allocate electric and thermal power in a combined heat and power microgrid. The market mechanism is formulated as a receding horizon constrained optimization problem, from which an optimal automated transactive procedure is developed. Its operation is distributed in nature and incorporates the most up-to-date electric and thermal load estimates and renewable generation. The results of the market clearing of the proposed microgrid μ DMM are the spot prices and schedules for electric and thermal power in addition to non-binding estimates of future prices and set-points. The performance of the μ DMM is illustrated using simulation studies of a Combine Heat and Power (CHP) microgrid model based on the Smart Polygeneration Microgrid (SPM) located on the University of Genova Savona Campus. The results show that the μ DMM has the ability to adapt to new information via updated forecasts and improve the performance of microgrid operation compared to a centralized method. This in turn makes the μ DMM attractive for use in μ EMS (microgrid Energy Management Systems) by allowing new energy resources to be added in a plug and play fashion.